SOCIAL ENTREPRENEURSHIP AND THE GENERATION OF OWN RESOURCES IN NGO FROM CEARÁ - Mendonça, Cristiane Maria Oliveira; Miranda, Rodrigo Oliveira; Ferraz, Serafim Firmo de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
Social Entrepreneurship proposes the innovation of ideas to solve social problems and the identification of opportunities arising from the market to finance social mission. The need for a greater financial autonomy and a smaller influence of their funders made social organizations, such as NGOs, seek to diversify their funding sources through the generation of their own resources. This research aims to investigate new alternatives developed by NGOs from Ceará, to finance their social projects. It is an empirical research, with a qualitative approach, where managers of commercial activities were interviewed, all from three NGOs located in Fortaleza: Instituto Atlântida, Vida Brasil - CE and Comunicação e Cultura. Through a descriptive analysis it was identified that the activities that generate their own resources are differentiated, both related to the type of service provided as the financial impact generated.